Tick-Borne Encephalitis Virus Adaptation in Different Host Environments and Existence of Quasispecies - Helmová, Renata; Hönig, Václav; Tykalová, Hana; Palus, Martin; Bell-Sakyi, Lesley; Grubhoffer, Libor (Viruses, 2020)
A highly virulent strain (Hypr) of tick-borne encephalitis virus (TBEV) was serially subcultured in the mammalian porcine kidney stable (PS) and Ixodes ricinus tick (IRE/CTVM19) cell lines, producing three viral variants. These variants exhibited distinct plaque sizes and virulence in a mouse model. Comparing the full-genome sequences of all variants, several nucleotide changes were identified in different genomic regions. Furthermore, different sequential variants were revealed to co-exist within one sample as quasispecies. Interestingly, the above-mentioned nucleotide changes found within the whole genome sequences of the new variants were present alongside the nucleotide sequence of the parental strain, which was represented as a minority quasispecies. These observations further imply that TBEV exists as a heterogeneous population that contains virus variants pre-adapted to reproduction in different environments, probably enabling virus survival in ticks and mammals.
Keywords: Encephalitis Viruses, Tick-Borne; Ixodes; TBEV; tick cell line; host alternation; Encephalitis, Tick-Borne; klíšťová encefalitida; Adaptation, Physiological; viry klíšťové encefalitidy; ledviny; genom virový; Female; mutace; Virulence; klíště; Kidney; flavivirus adaptation; zvířata; myši; virulence; Mice; Swine; genome mutation; buněčné linie; genetická variace; Genetic Variation; ženské pohlaví; Cell Line; Genome, Viral; neuroinvasiveness; Quasispecies; fyziologická adaptace; quasispecies; Animals; Mutation; prasata